Charting a new course for feminist psychology - Collins, Lynn H.; Dunlap, Michelle R., 1965-; Chrisler, Joan C. (Praeger, 2002)
Feminist psychology is vigorous, creative, and increasingly activist. This volume reflects women's diversity and incorporates strategies for social action and opportunities for political activism. It anticipates trends and developments in the psychology of women and feminist psychology. Chapters include those about women and self-esteem, leadership skills, welfare reform, spirituality, and domestic violence. The emphasis on social activism is unique. Unusual and cutting-edge research methodologies and techniques are also discussed.
Keywords: Feminist psychology.; Feminism.; Women -- Psychology.; Women -- psychology; Feminism; Psychologie féministe.; Féminisme.; Femmes -- Psychologie.; feminism.; PSYCHOLOGY -- Reference.; Feminist psychology; Women -- Psychology; Feministische psychologie.; Vrouwen.; Meisjes.; Cognitieve psychologie.; Paradigma's.; Feminismus; Psychologie; Aufsatzsammlung; Women's movement.; Women.; Womyn.